From Tradition to Digital Innovation: The Role of Artificial Intelligence in Driving the Transformation of Islamic Education - Mumtaz, Arina Sabila Aliffiya; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
Islamic education has a strong tradition of transmitting knowledge through halaqah, Islamic boarding schools, and madrasas, but the acceleration of digital innovation, especially artificial intelligence (AI), encourages changes in the way of learning, teaching, and managing educational institutions to be more adaptive without losing core values. This research aims to compile a systematic review of the role of AI in driving the transformation of Islamic education